2021
DOI: 10.1158/1535-7163.mct-19-1109
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Functional Avidity of CAR T Cells: Affinity, Avidity, and Antigen Density That Regulate Response

Abstract: Chimeric antigen receptors (CARs) are immunoreceptors that redirect T cells to selectively kill tumor cells. Given their clinical successes in hematologic malignancies, there is a strong aspiration to advance this immunotherapy for solid cancers; hence, molecular CAR design and careful target choice are crucial for their function. To evaluate the functional significance of the biophysical properties of CAR binding (i.e., affinity, avidity, and antigen density), we generated an experimental system in which thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…First, a number of experimental studies have reported that the T cell response is maximized at an intermediate affinity [50, 51, 52, 53, 54, 55, 56, 57, 58, 59]. Moreover, some of these studies have shown that an optimal affinity exists for both proximal and distal activation events (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a number of experimental studies have reported that the T cell response is maximized at an intermediate affinity [50, 51, 52, 53, 54, 55, 56, 57, 58, 59]. Moreover, some of these studies have shown that an optimal affinity exists for both proximal and distal activation events (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The implications of these considerations are perhaps most important for designing the next generation of immunotherapies. For example, identifying the optimal affinity and dose is central to the design of CAR T cell therapies [81, 82, 83, 57, 56, 58, 67, 84, 63, 59] as well as cancer vaccines [53, 54, 55, 56, 60]. Our information-theoretic approach provides a framework to guide the optimization of the T cell response via modification of the affinity or dose of the TCR-pMHC binding dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The avidity of the scFv against the antigen plays an important role on the functionality of the CAR T cells and its control may result in more effective therapies (55,56). Moreover, strategies combining the avidity of scFvs and the targeting of two molecules (or epitopes) may represent interesting approaches to increase the antitumoral efficacy and to reduce the toxicity (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing Ag delivery above this concentration threshold diminishes the regulatory phenotype [58], suggesting Ag dose can be a main design lever for controlling immune phenotype. Clinically relevant chimeric Ag receptors (CARs) and engineered T cell receptors (TCRs) are endowed with specific affinity for their target Ag, and increasing Ag affinity induces biphasic T cell responses [59][60][61]. This suggests that biophysical properties such as binding avidity and Ag density play key roles in overall T cell responses.…”
Section: Discussionmentioning
confidence: 99%